Analysis and experimental research on motion stability of wall-climbing robot with double propellers. (September 2021) - Liang, Peng; Gao, Xueshan; Zhang, Qingfang; Li, Mingkang; Gao, Rui; Xu, Yuxin
This paper presents a wall-climbing robot which can stably hold and move on the ground-wall surface. The robot uses propeller reverse thrust as an adsorption force and can adapt to the surface of several media materials. The influence of the robot's structural parameters on its power system is analyzed by comparing a single power system test and a robot prototype power test. A structural analysis of the robot is performed under two specific situations; when he is in transition from the ground to a small slope, and when he is on the slope. The force state of the robot is then obtained in different conditions. Experimental results show that the adjustment range of different rotor inclination angles of the robot, the width of the fixed rotor plate and the different near-ground distances, affect the traction of the robot. The robot motion performance and adaptability under different ground/wall environments are analyzed, by conducting the robot climbing experiment under a small slope, a vertical wooden wall surface and a vertical indoor wall surface. Stable adsorption and optimization tests are also performed. Moreover, the stability of the robot's motion is verified. Finally, a theoretical and experimental accumulation is laid for the realization of the smooth transition of the robot from the ground to the wall.